Stereotactic radiotherapy for treatment of juxtapapillary choroidal melanoma: 3-year follow-up. Issue 9 (3rd May 2009) - Krema, H; Somani, S; Sahgal, A; Xu, W; Heydarian, M; Payne, D; McGowan, H; Michaels, H; Simpson, E R; Laperriere, N
Abstract : Aims: To report the treatment outcomes and complication rates of stereotactic radiotherapy in the management of patients with juxtapapillary choroidal melanoma. Methods: A retrospective review of 64 consecutive patients with juxtapapillary choroidal melanoma, located within 2 mm of the optic disc, treated with stereotactic radiotherapy at Princess Margaret Hospital between October 1998 and January 2006. Results: The median age was 63 years. The median tumour height was 4.2 mm, and median largest basal diameter was 9.8 mm. The prescribed radiation dose was 70 Gy in five fractions over 10 days, and the median follow-up was 37 months. Post-treatment, the actuarial rates of local tumour control, metastases and survival at 37 months were 94%, 15% and 90%, respectively. Actuarial rates of radiation-induced complications at 37 months were neovascular glaucoma 42%, cataract 53%, retinopathy 81% and optic neuropathy 64%. Secondary enucleation was necessary for 10 patients (16%), in four patients for tumour recurrence and in six for painful neovascular glaucoma. Conclusions: Stereotactic radiotherapy offers a non-invasive alternative to enucleation and brachytherapy in the management of juxtapapillary choroidal melanoma with a high tumour control rate, however, at the expense of a significant rate of long-term ocular complications.